How does educational background shape the perception of cybercrime? - Uhl, Andrzej (Varstvoslovje, 2022)
Purpose: The technical dimensions of cybercrime and its control have rendered it an inconvenient subject for many criminologists. Adopting either semantic (legal) or syntactic (technical) perspectives on cyber criminality, as theorised by McGuire, can lead to disparate conclusions. The aim of this paper is to examine how these perspectives and corresponding educational backgrounds shape opinions on cybercrime and cybercrime policy. Design/Methods/Approach: To address this research question, we first provide a non-exhaustive review of existing critical literature on a few selected controversial issues in the field, including cyber vigilantism, file sharing websites, and political hacking. Based on these areas, we developed an online survey that we then distributed among students of law and computer science, as well as to a ‘non-cyber contrast group’ including mainly students of philology and philosophy. Findings: Statistical analysis revealed differences in the way respondents approached most of the issues) to most of the issues, which were sometimes moderated by the year of studies and gender. In general, the respondents were highly supportive of internet vigilantism, prioritised the cybercrimes of the powerful, and encouraged open access to cybersecurity. The computer science students expressed a lower fear of cybercrime and approved of hacktivism more frequently, while the law students affirmed a conservative vision of copyrights and demonstrated higher punitiveness towards cyber offenders. Interestingly, the computer science students were least likely to translate their fear of cybercrime into punitive demands. Research Limitations/Implications: The findings support the distinction between various narratives about cybercrime by showing the impact of professional socialization on the expressed opinions. They call for a consciously interdisciplinary approach to the subject and could be complemented by a comprehensive qualitative inquiry in the perception of cyber threats. Originality/Value: The authors wish to contribute to the understanding of the construction of cybercrime on the border of criminal law and computer science. Additionally, we present original data which reveal different views on related issues held by potential future professionals in both areas.
Keywords: cyber punitiveness; cyber victimisation; cybercrime; internet crime; internetna kriminaliteta; kibernetska kaznovanost; kibernetska kriminaliteta; kibernetska viktimizacija